Respuestas

2011-11-29T02:37:34+01:00

la edad de b:x

la edad de a:x-14                              finalmente: la edad de b es:35

total:56                                                                entonces:la edad de a es la  

ahora                                                                                  edad de b-14

x+x-14=56                                                                            es:35-14=21

     x+x=70                                                            la edad de a es:21

       2x=70                                                            y la de b es:36

         x=70/2                                                            a+b=56

         x=35                                                             21+35=56 

15 4 15